ON THE TIME LIMITING OF THE COURT ACTS IN CIVIL PROCEDURE - Keča, Ranko (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
Abstract: The efficiency of the legal protection in litigation presents one of the main reasons for the quite frequent legislature changes of the Civil Procedure. To achieve this goal a number of new provisions was introduced. Given meaning has a new regulation which tends to limit the duration of the litigation as well. Litigation timeframe obligation is in that sense introduced, and on the other hand in number of situations court management acts are time limited. The non complying of the time limits remains non sanctioned in litigation sense, but it represents a cause for a disciplinary responsibility of the judge. This mechanism was introduced to speed up litigation and to fulfill parties’ right for a judgment in reasonable time and it could achieve these goals, but only with creating real prerequisites for successful functioning of the courts. If not it will transform itself in just another mean of the pressure on the judges. Keywords: legislature changes of Civil Procedure; efficiency of the litigation; litigation timeframe; time limits for the court acts; disciplinary responsibility of the judges.